Physio-Chemical Properties, Consolidation, and Stabilization of Tropical Peat Soil Using Traditional Soil Additives â A State of the Art Literature Review - Ahmad, A. (Springer Verlag, 2021)
Peat is formed by the degradation of plants and animals in the lack of oxygen and is widely known for its very weak geotechnical characteristics. This is the reason to be considered as an unsuitable foundation soil for construction activities. Several attempts have been made to characterize and stabilize peat soil to make construction viable. This study encapsulates an extensive literature review of the available published data for Atterberg limits, consolidation, and stabilization of peat soil using traditional additives, especially cement and lime. Moreover, peat formation and distribution around the world are also discussed. The analysis of the gathered data shows that peat soils having a high amount of fibers may suffer a large amount of secondary consolidation when the load is applied. Besides, the compressibility factors vary for Malaysian peat due to different water and organic contents. The improvement of peat soil is challenging and expensive, requiring an extra amount of stabilizer for the initiation of the stabilization process. However, the optimum and threshold stabilizerâs dosage for peat is also a challenging task to predict due to several factors affecting the stabilization process. Lastly, the study concludes with recommendations on the implication of the fall cone and thread rolling tests for the determination of Atterberg limits of fibrous peat, effective consolidometer for peat, and utilization of traditional additives for peat soil stabilization. Â© 2021, Korean Society of Civil Engineers.